THE FOLK MUSIC AND DANCE’S AS A MEANS OF AESTHETIC EDUCATION OF THE DAGESTAN CHILDREN - Basirova, Karina Kasumovna (History, Archeology and Ethnography of the Caucasus, 2020)
The paper examines work training, physical upbringing of children with the use of national music and dances from the ethnographic standpoint. The paper provides examples of successful education of children through national music (songs, dances), the application of original musical genres, national instruments, melodies, dances, dance and singing etiquette, which are partially preserved to this day. The importance of preserving national traditions, including musical ones, as well as conscious cultural policy are highlighted. The technique of performing dances and songs in Dagestan is inextricably linked with the process of upbringing children. The features and the role of ethno-musical traditions in a multilayered stratum of identities of Dagestan peoples are revealed. The core of the musical culture of Dagestan peoples lies in the rhythm (temporary musical factor) and intonation (high factor), which conditioned the integrity of instrumental and dance traditions. Songs and dances, chaban’s pipe, the call for “zurnach” (zurna player) and drum rolls always accompanied lives of the mountaineers. The mountaineer’s dance “lezginka” can be considered national, since no festival in Dagestan would pass without it. Of great importance is the familiarization of young children with the national culture, traditions of the Dagestan peoples, their spiritual values through musical culture. The inclusion of the spectrum of musical culture in the context of cultural policy can ensure the effectiveness of the socio-cultural development of the region.